1993
DOI: 10.1093/jmedent/30.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cliff Swallows, Ectoparasites, and an Alphavirus in West-Central Oklahoma

Abstract: Approximately 250 isolates of a newly recognized virus, related to western equine encephalitis virus (family Togaviridae, genus Alphavirus), were obtained from cimicid bugs, Oeciacus vicarius; Cliff Swallows, Hirundo pyrrhonata; and House Sparrows, Passer domesticus in a study area in west-central Oklahoma at Buggy Creek and Caddo Canyons. Antigenicity of the virus strains varied slightly from isolate to isolate. This paper summarizes the ecology of the area by describing in general the flora and fauna there.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 0 publications
0
65
0
Order By: Relevance
“…Because the number of swallow bugs at a site is correlated with cli¡ swallow colony size, the population sizes of either organism might reach critical thresholds for sustaining BCR virus infection. Both the bug and the bird are closely associated with BCR virus and its sibling strain FM virus (Hayes et al 1977;Rush et al 1980;Scott et al 1984;Hopla et al 1993). For example, the results presented here show that relatively high percentages of swallow bugs are infected and preliminary data on the presence of BCR virus antibody in cli¡ swallows show at least 9% of adults with detectable antibody titres (n 245 birds) (C. R. Brown, M. B.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Because the number of swallow bugs at a site is correlated with cli¡ swallow colony size, the population sizes of either organism might reach critical thresholds for sustaining BCR virus infection. Both the bug and the bird are closely associated with BCR virus and its sibling strain FM virus (Hayes et al 1977;Rush et al 1980;Scott et al 1984;Hopla et al 1993). For example, the results presented here show that relatively high percentages of swallow bugs are infected and preliminary data on the presence of BCR virus antibody in cli¡ swallows show at least 9% of adults with detectable antibody titres (n 245 birds) (C. R. Brown, M. B.…”
Section: Discussionmentioning
confidence: 68%
“…These viruses tend to be vectored by invertebrates (usually mosquitoes) and ampli¢ed and spread over large geographical areas by birds. BCR virus was ¢rst isolated in the early 1980s from swallow bugs collected at a cli¡ swallow colony along Buggy Creek in Grady County, west central Oklahoma (Loye & Hopla 1983;Hopla et al 1993). BCR virus is very similar to another alphavirus, Fort Morgan virus (FM), which is also associated with cli¡ swallows and swallow bugs (Hayes et al 1977;Calisher et al 1980;Scott et al 1984).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BCRV shares structural similarities with other alphaviruses in the WEEV complex, it is primarily transmitted by the cimicid swallow bug (Hemiptera: Cimicidae, Oeciacus vicarius), rather than by mosquitoes, and is not considered a pathogen of humans or domesticated animals (Griffin, 2001). Buggy Creek virus (BCRV) is known to be amplified by only two vertebrate hosts, the Cliff Swallow (Petrochelidon pyrrhonota) and the introduced House Sparrow that usurps the mud nests that Cliff Swallows build (Hayes et al, 1977;Hopla et al, 1993). Adult and nestling House Sparrows are exposed to and fed upon by the hematophagous swallow bugs (O'Brien, pers.…”
Section: Introductionmentioning
confidence: 99%
“…Buggy Creek virus is a single-stranded, positive-sense RNA alphavirus (Hopla et al, 1993). Fort Morgan virus (Calisher et al, 1980), also found in swallow bugs, is a strain of BCRV (Pfeffer et al, 2006;Padhi et al, 2008); thus, FMV and BCRV are synonymous.…”
Section: Study Organismsmentioning
confidence: 99%